Development of herb education in Begunitsky Agro-technological College - Galambosi, B.; Kirakosyan, G. M.; Dembickaya, E.; Lapshin, A.; Nemtshenko, N. F.; Kauppinen, S.; Sorvari, J.
Appendix 1. Participation in different congresses with posters and lectures between 2003–2010. Appendix 2. List of scientific publications between 2003–2012. Appendix 3. Scientific papers, congress abstracts and popular articles in SPECICROP-project 2012–2014. Appendix 4. The content of Finnish and Russian herb cultivation book : Cultivation of herbs and medicinal plants under Nordic climatic conditions suitable for North-West Russia and South-East Finland During the last decade the interest for domestic grown herb raw materials have increased among pharmaceutical companies in the Leningrad region, Russia. There are eight vocational agricultural colleges in the Leningrad region, and none of them teaches herb cultivation. There is a lack of cultivation expertise, also in herb cultivation education material. Due to the cross border cooperation with the support of EU Interreg and ENPI programs, during 1995–2014 several projects have resulted specialisation for herb education in the Begunitsky Agrotechnological College, in connections with Finnish institutes. Due to the similar northern climate conditions in regions of South-East Finland and North-West Russia, the cooperation focused on cold tolerant medicinal plants, and berry and fruit plants. In these projects we made efforts for transferring the experiences of organic cultivation obtained in small-scale herb farms in Finland into Russia. During the last 3-year project “Special crop education for economic development in North-West Russia and South-East Finland SPECICROP” we strengthened the preconditions of the professional education in the College by creating of demonstration herb garden with 30 species, renovation of the greenhouse and the herb-vegetable educational cabinet supplied by an infrared experimental dryer for herbs. For increasing the professional skills of teachers and entrepreneurs study trips were organized in family size herb farms in Finland, in fruit institutes and companies around Moscow, and in herb-processing companies in Altai. Regular ...